A Thematic Catalogue of the Instrumental Music of Martino Bitti (1655/6–1743). Issue 1 (2015) - Talbot, Michael
Abstract : Martino Bitti (1655/6–1743) was the leading violinist-composer working in Florence during a long period stretching from Corelli's first published works to the mature years of Vivaldi. Ironically, his nine sonatas for wind instruments are better known today than the 27 solo sonatas for his own instrument, the violin, which constitute a corpus of great technical accomplishment and musical expressiveness. Since the publication of a critical edition of Bitti's violin sonatas is currently in progress, the moment is right to present a thematic catalogue of his instrumental music, which forms the second part of the article. The first part comprises an updated biography of the composer (which for the first time proposes that Bitti briefly visited England) and a general evaluation of his highly distinctive musical style.